Qualitative characteristics accounting information of kariah mosque: A concept paper / Masita Hassan … [et al.] - Hassan, Masita; Abdullah, Salina; Mohd Sehat, Rahayu; Abu Bakar, Norlinda Tendot (2017)
All financial transactions should be included in organisations' reports in order to provide complete financial information to its primary and other users. Therefore, financial reports prepared by kariah mosque should encompass qualitative characteristics that would assist users in decision making. Malaysian Accounting Standard Board (MASB) has outlined the characteristics that should be included in business organisation financial report. However, kariah mosques are categorized under non-profit organisation, thus, characteristics may differ from profit making organisation. This study is objectively to investigate the understanding of qualitative characteristics and the usefulness of financial information that presented in kariah masjid‘s financial report. The study will use qualitative characteristics that adopted from Malaysian Accounting Standard Board (MASB) namely relevance, faithful representation, comparability, verifiability, timeliness and also other characteristics that suggested from previous literature. The study will use self-administer questionnaire, distributed to users (working committees, funders, donors) and preparer of kariah masjid‘s financial report. It is estimated that the understanding the quality of financial report would be different among users and preparers.